Impact on One Element of the Water Hydrological Cycle Changes the Climate - Singamayum Ashif (Global Journal of Plant and Soil Sciences, 2023)
An important link in transformations in a single process of water circulation is the dissolution of minerals and fertilizers from the bottom and banks of rivers and underground canals and their delivery to plants and animals. Water, as a vehicle - delivers solutes to living cells and leaves with waste. The quality of exhaled moisture and waste is highly individual, both within species and be- tween species of biota.